Evaluation of the Efficacy of Daily Consumption of Eucommia ulmoides Leaves in A Sample of Healthy Volunteers - Ibrahim, Doa’a Anwar (Asian Journal of Pharmaceutics (AJP), 2018)
Context: More than 80% of the population around the world believes with traditional medicine to overcome the side effects, resistance, and cost of synthetic medications. Herbal medicines take the upper hand in this manner as they safe, effective with low cost. Eucommia ulmoides (EU) belongs to Eucommiaceae family widely cultivated in China. It contains many active compounds and used traditionally and pharmacologically as cardioprotective, neuroprotective, and hepatoprotective effects due to antioxidant activities. Aims: The aim of this study is to evaluate the efficacy of EU leaves if consumed daily. Settings and Design: This study was done in Faculty of Pharmacy-Clinical Pharmacy and Pharmacy Practice unit-Pharmacology Unit at University of Science and Technology after taking Permission from the University Ethics Committee - Sana’a, Yemen. Methods and Material: A total of 26 healthy volunteers (15 male and 11 female) participated in this study. They allowed to drink 2 g of EU leaves twice daily (tea) for 4 weeks. The parameters were taken before and after the study that including body mass index, systolic blood pressure (SBP), diastolic blood pressure, and mean arterial pressure (MAP). In addition, biochemical studies were done, including the measurement of fasting blood sugar, complete blood count, and lipid profile; liver function tests, kidney function tests, electrolytes, and sex hormones. Statistical Analysis Used: Results of representative values were expressed as a mean ± standard error of the mean. Comparisons between two groups were made using a paired t-test (SPSS Version 21). P < 0.05 were considered statistically significant. Results: The outcomes of this study showed that EU reduced blood pressure (SBP, DBP, and MAP), lipid profile (cholesterol, triglyceride, and low-density lipoprotein cholesterol), and kidney function tests (urea and creatinine), besides that it improved hematopoiesis and reduced inflammatory cell. Conclusions: It is suggested that the EU can be used as an adjuvant therapy due to its beneficial antihypertensive, dyslipidemic, nephroprotective, hematopoietic, and anti-inflammatory effects as well as estrogenic-like effect